Efektivitas Media Canva dalam Meningkatkan Motivasi dan Hasil belajar Matematika Sekolah Dasar Tahun 2022–2025: A Systematic Literature Review - Imam Taufiq; Adrias Adrias; Fitrawati Fitrawati; Yanti Fitria (Lembag, 2025)
The advancement of digital technology has significantly transformed 21st-century education. One of the widely used tools in elementary mathematics learning is Canva, which enables interactive, visual, and creative instruction. This study employed a Systematic Literature Review (SLR) to examine the trends, effectiveness, and challenges of Canva use in mathematics learning from 2022 to 2025. Data were collected through Publish or Perish linked to Google Scholar, resulting in 24 eligible studies. The findings reveal a strong upward trend, with 100% of studies using Canva as the main medium and 70.8% applying R&D approaches. In terms of effectiveness, 95.8% of studies reported improved learning outcomes, and 87.5% noted higher student motivation and engagement. Canva effectively enhances conceptual understanding of abstract mathematical topics and supports project-based learning. Major challenges include limited teacher digital skills (66.7%) and unequal access to ICT (58.3%). Overall, Canva is identified as an effective, innovative, and adaptive digital learning medium aligned with the principles of Kurikulum Merdeka, which emphasizes active, contextual, and student-centered learning.